Polityka (nie)pamięci o sowieckiej przeszłości Gruzji w czasie prezydentury Micheila Saakaszwilego .......... 47 - Pająk, Anna (Rewolucja rosyjska. Spuścizna : międzynarodowe echa rewolucji, 2017)
THE POLICY OF (NON-)REMEMBRANCE OF GEORGIA’S SOVIET PAST DURING MIKHEIL SAAKASHVILI’S PRESIDENCYAfter the October Revolution and the collapse of the Russian Empire, the Democratic Republic of Georgia was founded, which was occupied by the Bolsheviks in 1921, thus launching a seventy-year period of Soviet history of Georgia. Mikheil Saakashvili was the third president of an independent Georgia after the collapse of the Soviet Union. When he came to power in 2003 he undertook activities in almost all spheres of social and political life, characterized primarily by the anti-Russian and anti-Soviet dimension. The article entitled “The policy of (non-)remembrance of Georgia’s Soviet past during Mikheil Saakashvili’s presidency” is an analysis of the historical policy activities undertaken by the Georgian president, which were to fundamentally destroy the Russian and Soviet past of Georgia, and thus shape a new type of society, uncritically appealing to the Europeanness of Georgia, transforming the memory of the Soviet legacy from “70 years of the soyuz” to “70 years of occupation”. The text is mainly based on internet articles and publications of Georgian academics as well as the author’s own research.